(1, 1) L-space knots. (20th March 2018) - Greene, Joshua Evan; Lewallen, Sam; Vafaee, Faramarz
Abstract : We characterize the (1, 1) knots in the 3-sphere and lens spaces that admit non-trivial L-space surgeries. As a corollary, 1-bridge braids in these manifolds admit non-trivial L-space surgeries. We also recover a characterization of the Berge manifold among 1-bridge braid exteriors.